DIGITAL PUBLIC SPACE AND THE FACE OF INDONESIAN POLITICAL EDUCATION - Muhammad Farid; Reiza Praselanova (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
Reporting on digital mass media often vulgarly takes a position in favor of interests. Is the partiality direct, or is it in the form of framing? Television shows and newspaper reports have even become the public's 'breakfast'. The mass media is increasingly becoming a determinant of the cognitive menu of people's daily thoughts. And not a few are lulled into believing that it is the most true and authentic. This article directs attention to the role of social media as a digital public space for Indonesian people's cognition. By using Jurgen Habermas' theoretical frame on the public sphere, the author concludes that digital media plays a significant role in shaping the public's way of thinking which tends to be co-opted to political power and capital owners. This way of thinking then forms a mass culture that is prone to authoritarianism. The findings of this research also serve as a warning to stakeholders who must be more vigilant in anticipating the globalization of digital media which can actually change the face of political education and the future of our democracy.